HUBUNGAN POWER OTOT TUNGKAI TERHADAP HASIL SMASH PADA TIM BOLA VOLI LASKAR API-API BANDAR LAKSMANA - Fauzi, Fauzi; Vai, Aref; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to determine the relationship between arm andshoulder muscle power and smash performance in volleyball. The research uses acorrelation method. The study population consists of 12 volleyball players from the"Lascar Api-Api Badar Laksmana" team, using a saturated sampling technique. Theinstruments used are the vertical jump test and smash test. The data obtained wereanalyzed using descriptive statistics, normality tests, and t-tests. The normality testresults with Kolmogorov-Smirnov showed an asymp. Sig. (2-tailed) value > 0.05,indicating a normal distribution. Based on the Pearson product-moment correlationanalysis, the calculated correlation coefficient (r) is 0.838, with an r table value of0.602. The correlation is positive, indicating that the higher the leg muscle power involleyball players, the better their smash performance, and conversely, the lower the legmuscle power, the poorer their smash performance.Key Words: Leg Muscle Power, Smash Performance, Volleyball